Analysis of recombinant group B streptococcal protein ScaAB and evaluation of its immunogenicity - Vorobieva, E I; Meringova, L F; Leontieva, G F; Grabovskaya, K B; Suvorov, A N (Folia microbiologica, 2005)
Group B streptococcal (GBS) gene encoding the putative lipoprotein and adherence factor ScaAB was cloned and expressed in E. coli. Recombinant ScaAB protein was isolated. Signal sequence of ScaAB was found to be cleaved in the E. coli host. ScaAB recombinant protein was immunogenic in mice and antibodies against this protein were discovered in mice sera after GBS infection. The perspectives of the use of ScaAB protein in GBS vaccine are discussed.
Keywords: Molecular Sequence Data; protilátky bakteriální; Streptococcal Infections; membránové proteiny; sekvence aminokyselin; Membrane Proteins; Bacterial Adhesion; rekombinantní proteiny; Streptococcus agalactiae; Mice; bakteriální adheze; Bacterial Proteins; Immunization; zvířata; Amino Acid Sequence; Antibodies, Bacterial; myši; streptokokové infekce; molekulární sekvence - údaje; imunizace; bakteriální proteiny; Recombinant Proteins; Animals